Access to Vinyl Ethers and Ketones with Hypervalent Iodine Reagents as Oxy‐Allyl Cation Synthetic Equivalents. Issue 41 (13th August 2020) - Declas, Nina; Waser, Jerome
Abstract: We report an Umpolung strategy of enol ethers to generate oxy‐allyl cation equivalents based on the use of hypervalent iodine reagents. Under mild basic conditions, the addition of nucleophiles to aryloxy‐substituted vinylbenziodoxolone (VBX) reagents, easily available in two steps from silyl alkynes, resulted in the stereoselective formation of substituted aryl enol ethers. The reaction was most efficient with phenols as nucleophiles, but preliminary results were also achieved for C‐ and N‐ nucleophiles. In absence of external nucleophiles, the 2‐iodobenzoate group of the reagent was transferred. The obtained aryl enol ethers could then be transformed into α‐difunctionalized ketones by oxidation. The described "allyl cation"‐like reactivity contrast with the well‐established "vinyl‐cation" behavior of alkenyl iodonium salts. Abstract : Access to oxy‐allyl cation equivalents from alkynes by hypervalent iodine reagents is described. The stereoselective transformation of vinylbenziodoxolones (VBXs) provides aryl enol ethers bearing an allylic ether or ester group and corresponds to an Umpolung of the nucleophilic reactivity of enol ethers. The obtained products are easily transformed into α‐difunctionalized ketones under oxidative conditions.